Design and construction of the 3D printer two-stand, controlled Arduino Mega 2560 R3 CH340G - Agus Edy Pramono; Nazhmi Fadhila; Rafi Pradaya Andareska; Feri Nugroho Adi Noto; Iman Setiyadi; Aminudin Zuhri; Yohanes Patrik (Recent in Engineering Science and Technology, 2024)
The need to show the geometry of a workpiece of a component or system on a certain scale and three-dimensionality can be realized through a three-dimensional printing press. This paper explains the techniques and how to design a three-dimensional printing machine and test product printing. The three-dimensional printing machine has been successfully created and built, and the printing test shows the results corresponding to the machine's specifications. The design and fabrication of printer 3D printing machine for PLA filament thermoplastic material has been successfully done. This machine implements an Arduino Mega 2560 R3 CH340G-based control system. The specifications of the 3D printing machine are as follows: Layer height = 0.2 [mm]; Infill density = 20%; Maximum Printing temperature = 240°C; Build plate temperature = 60°C; Print speed = 60 [mm/s]. The input comes from an AC power source that is converted to DC with an Input Power supply of 12 Volt 20 A. The machine has been tested, and parts with geometry are produced according to the machine's specifications.